Backwardness as a condition to critique: Paulo Arantes on The German Ideology (Revista Eletrônica Estudos Hegelianos, 2024)
In this article, we present Paulo Arantes’ new interpretative approach to the manuscripts of The German Ideology: the understanding that the fundamental problem of Dialectic – the mediation between the universal and the particular, or, the settling of accounts between the idea and the effective reality – persists precisely in Marx and Engels’ consideration of the political and economic backwardness of Vormärz Germany and in the way in which post-Hegelian philosophy expresses this backwardness. By emphasizing Stirner’s critique of universals as fundamental to the Marx and Engels’ critique of ideology, Arantes both differs from the history of the classical reception of these manuscripts, which centralizes the authors’ critique of Feuerbach, and anticipates the widespread position in recent bibliography on Marx and Engels, without resorting, however, to philological studies, as has been done in the literature surrounding the MEGA² project since the 1990s. With this, the text that is commonly seen as a departure from philosophy towards the so-called historical materialism can be read as a “determinate negation [to idealism] [...] whose materialism, it can be seen immediately, does not stop at reducing ideas to the literal matter that supports them” (Arantes, 1996, p. 369).